The Integration of Cultural Content in English Textbook When English Rings a Bell for 7th Graders of Junior High School - Nurlaila Husain; Hilda Adrin; Sri Rumiyatiningsih Luwiti (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2022)
This research investigates the culture in the English textbook "When English Rings a Bell" for VII Grade Junior High School, written by Siti Wachidah et al. The present work relied on a content-analyzed documentary study. Furthermore, this research used documentary analysis by categorizing the findings into four types based on theory of Moran (2001) about language learning cultural functions as a tool of content analysis: language for participating in culture, language to describe culture, language to interpret culture, and language to respond to culture. A descriptive analysis was applied to read, identify, and display data by culture. According to the result, all chapters in the book incorporate the four cultural knowing frameworks. Cultural content is used 43 times to refer to description, knowing about; 21 times to refer to cultural participation, knowing how; 19 times to refer to interpretation, knowing why; and 10 times to refer to response, knowing oneself. In conclusion, the textbook is compatible in the cultural context.  This is shown by the fact that the textbook uses names, actions, places, and characters from the source culture, i.e., the Indonesian culture.